Demographic Profile and Pattern of Presentation of Organophosphorus Poisoning at Tertiary Care Hospital Agra (Indian Journal of Forensic Medicine & Toxicology, 2020)
India is agriculture dominant country and organophosphorus commonly used by former in agriculture field.Therefore, Organophosphorus poisoning is common India. Study done at emergency department to knowthe pattern of sign and symptoms presentation at the time of admission. Total number of cases was 160, outof them 102 (64%) were males and only 58 (36%) were females. Male to female ratio was 1.75:1. farmers 61(38%) were commonly affected, followed by 35(22%) of patients were housewives and 26 (16%) of patientswere students. symptoms presented were vomiting 150 (93.75%) and salivation 150 (93.75%), followedby sweating 147 (91.88%), lacrimation 102 (63.75%) and blurring of vision 80 (50%), breathlessness(40%), faecal incontinence (31.88%), urinary incontinence (18.13%), headache (18.13%) and convulsion(10%). commonest signs were smell of poison 150 (93.75%), followed by tachypnoea 134 (83.75%),altered consciousness 115 (71.88%), miosis 86 (53.75%), fasciculation 70 (43.75%), tachycardia (36.25%),bradycardia (28.13) and pulmonary oedema (06.25%). Increased body secretions were the commonestpresentation then other symptoms followed were blurring vision, tachypnoea altered consciousness, andrespiratory symptoms. It can be helpful to make diagnosis and take awareness, preventive measures aboutorganophosphorus poisoning.